Occupational Health - Korhan, Orhan (IntechOpen, 2017)
Occupational Health deals with all aspects of health and safety in the workplace and has a strong focus on primary prevention of hazards. A wide array of workplace hazards presents risks to the health and safety of people at work, which include physical factors, adverse ergonomic conditions, chemicals, biological agents, allergens, and a complex network of safety risks. This book covers topics from health and safety management, occupational medicine, work-related musculoskeletal disorders, and occupational protection. Thus, it can be utilized as a guide to identify and analyze hazards, assess risk, apply risk reduction strategies, and manage process safety for various occupations.